(untitled) (Research, Society and Development, 2021)
This study aims to present the role of accounting as a support tool for organizations regarding the quality of accounting information applied in business strategies. The relevance of this research is justified because, in addition to the science about the dynamics of the companies’ equity, it is necessary to have knowledge of all its extension for a situation of more profitable operations, making the role of accounting information fundamental for the organizations’ strategies. As for the methodological aspects, it is characterized as descriptive and exploratory research, with a qualitative approach, with the use of documentary research and an unstructured interview that was carried out in a business group that operates in different segments. Preliminarily, it was verified the real importance of Information Technology (IT) in the process of dissemination of accounting information combined with the use of tools aimed at organizational strategic management.